Experimental study of using Synthetic Wax Additives (Sasobit) to design Warm Mix Asphalt - صقور اياد; بسام سلطان (Latakia University Journal -Engineering Sciences Series, 2024)
In the last years, many researchers studied production of warm asphalt concrete by using organic, chemical and water-bearing additive. The purpose of this research is to evaluate the use of Sasobit additive in the manufacture of warm asphalt mixes and studying the changes in properties of warm mix asphalt compared to the properties of hot mix asphalt. The bitumen binder and Sasobit additive samples used in this work has been characterized. Two types of asphalt mixtures were done according to the Marshall method: Hot mixtures and warm mixtures containing different percentage of Sasobit additive (1, 1.5, 2)% by weight of bitumen binder, then the changes in the properties of warm asphalt mixtures modified with Sasobit additive were investigated and compared with reference mixtures. Results of Marshall tests showed an increase in the ideal asphalt ratio in warm asphalt mixtures compared to hot, low stability and density of WMA and indicated to success of the Sasobit additive in manufacture of warm asphalt mixes, at a suggested percentage of 1.5% of the total weight of bitumen binder, in which the physical and mechanical properties of the warm mix asphalt were close to the properties of the hot mix asphalt, with the need to study WMA resistance against moisture damage.